Wissensbasierte Navigation für die lärmreduzierte Auslegung rotierender Maschinen in der Produktentwicklung - Küstner, Christof; Wartzack, Sandro (Design for X - Beiträge zum 25. DfX-Symposium, 2014)
Today, product developer face the challenge taking not only the requirements for mechanical properties of a product into account, but also other requirements like the acoustical properties, for instance. The problem is that important product properties like the acoustical properties are only revealed in the later development phases. Normally product developers elicit knowledge from experts to fulfil these additional requirements. In this contribution, an approach for a knowledge-based navigation for the development of noise-reduced machines is presented. Therefore the knowledge identification, acquisition, formalization and the implementation in an assistant system are described. This approach contributes to the improvement of knowledge transfer from expert to product developer vice versa.
UnivIS-Import:2015-10-26:Pub.2014.tech.FT.FT-KLMEFK.wissen
Keywords: knowledge-based navigation; assistant system; noise-reduced development; activities and decisions